Analytical Validation of a New Immunoenzymatic Method for the Measurement of Feline Parathyroid Hormone in Cats with Chronic Kidney Disease - Jari Zambarbieri (MDPI AG, 2021)
The determination of parathyroid hormone (PTH) in cats could be of clinical utility in many metabolic disorders, such as renal diseases, hypercalcemia, or nutritional imbalances. However, the available methods for the measurement of feline PTH are limited, not widely available, and need radioimmunoassays. The aim of this study was to perform the analytical validation of a new immunoenzymatic method for the measurement of feline PTH. Thirty-eight cats affected with chronic kidney disease (CKD) were included. PTH was measured using a two-site immunoenzymatic method validated in humans and dogs (ST AIA-PACK® Intact PTH, Tosoh Bioscience, Tessenderlo, Belgium). The analytical validation provided the evaluation of precision (intra-assay and inter-assay), accuracy (linearity under dilution (LUD) and spike recovery test (SRT)), and the storage stability of serum samples at 20 °C, 4 °C, and −20 °C. The method showed good precision (intra-assay CVs (coefficient of variations) 3.19–9.61%; inter-assay CVs 9.26–15.28%). In both the intra- and inter-assays, the highest imprecision was found with the low concentration pool (9.61% and 15.28%) and accuracy (LUD and SRT r2 = 0.99, p < 0.001), while the stability was optimal up until 7 days at −20 °C (−7.7%). The method was successfully validated in cats, allowing its future use in diagnostic procedures.